Quantum transport evidence of isolated topological nodal-line fermions - Hoil Kim; Jong Mok Ok; Seyeong Cha; Bo Gyu Jang; Chang Il Kwon; Yoshimitsu Kohama; Koichi Kindo; Won Joon Cho; Eun Sang Choi; Youn Jung Jo; Woun Kang; Ji Hoon Shim; et al. (Nature Communications, 2022)
Clear electronic transport signatures of topological nodal-line semimetals have been lacking due to their complex electronic structure and the presence of topologically trivial states. Kim et al. demonstrate that the quantum transport response in slightly hole-doped SrAs3 is dominated by nodal-line fermions.